Gengzi reflections: how did Chinese culture evolve in the last 180 years. Issue 3 (3rd July 2022) - Tang, Yinshan
ABSTRACT: In its history, Chinese culture has experienced three big waves of developments. The first one was in the Warring State Period, instigated by a large number of philosophers who laid the foundations of Chinese culture. The second was the introduction of Buddhism and its final integration with Confucianism and Daoism in Southern Song dynasty (1127–1279). The third was represented by the introduction of science and social beliefs from the West (from 1840 onwards). This paper focuses on the cultural changes since 1840, from the Opium war to COVID-19 expands three Gengzi cycles. During the past 180 years, China has experienced one the most turbulent eras of its history, associated with immense culture changes. . In the recent 60 years, China has focused on economic development. The fast economic development and their response to COVID-19 have demonstrated that a system with Chinese characteristics will become the de facto system for China.